Consciência fonológica, conhecimento lexical e repetição de pseudosinais da LIBRAS em crianças surdas bilíngues: a influência da estimulação precoce. - Roldão, Michelle Mélo Gurjão (2025)
Phonological development is considered primordial for constructing the necessary foundation for later linguistic development, encompassing morphological, syntactic, semantic, and pragmatic levels. However, according to Cruz (2008, 2016), this process usually occurs late in deaf children, due to the period when the acquisition of sign language (SL) was initiated, especially if considering deaf children of hearing parents, due to their lack of knowledge in relation to SL. Thus, it is essential to highlight the importance of early stimulation so that the child can have access to SL from the first years of life. This importance is also emphasized by Vygotsky, who is one of the precursors in the studies of disabled people, and who paved the way for this study to enhance the understanding of the acquisition and development of language by deaf children. In addition to the research, more studies were accessed, making it possible to better grasp these processes as a basis for initial and subsequent linguistic development. Taking this into account, the main aim of the present study is to analyze the performance of the phonological awareness of the Brazilian Sign Language (Libras in Portuguese), the lexical knowledge and repetition of pseudo-signals by deaf bilingual children who had an early stimulation program, comparing them to deaf bilingual children who did not have equal opportunity. The following scholars’ findings provide the theoretical support for this research: Mayberry, Morford, Quadros, and Fusellier-Souza, in the area of sign language acquisition; Campello, Guimarães, Cruz and Quadros, about the specific aspects regarding Libras lexical knowledge and repetition of pseudo-signs. As far as the education of deaf people is concerned, the theoretical framework is based on Vygotsky, Cavalcanti, and Quadros. The work with early stimulation of language in SL was grounded on Grassi, Stumpf, and Linhares. Methodologically, it is a comparative, transversal study of qualitative-quantitative nature, with deaf students as participants from the early years of elementary, bilingual schools of São Paulo and Paraíba. The children underwent the Phonological Awareness Test in Libras (TCF-Libras in Portuguese), proposed by Cruz (2016), and the Repetition Thesis of Pseudosignals (a test developed by a team of the Bilingual Bimodal Development Project), while the parents responded to a semi-structured interview about the linguistic, auditory and educational aspects of their deaf children. For quantitative data analysis, the statistical test of Mann-Whitney was used. Bardin inspired qualitative data analysis. The results obtained after the application of the Phonological Awareness Test of Libras (including the lexical knowledge test) revealed significant differences between the group of children who participated in early development stimulation, who showed a better performance - and the children who did not have the same opportunity, reinforcing the positive impact of early exposure to Libras. The Pseudosignals Repetition Test showed no statistically significant differences between groups. The involvement of the family in the SP group and the continuity of bilingual education in this group were key factors for its students to show greater linguistic progress. The findings of this research contribute to the field of language acquisition and the development of more effective educational practices aimed at deaf children, in addition to reinforcing the importance of acquiring sign language as early as possible.